2004
DOI: 10.4049/jimmunol.173.6.3935
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Notch1 Function by In Vitro T Cell Differentiation ofPax5Mutant Lymphoid Progenitors

Abstract: Signaling through the Notch1 receptor is essential for T cell development in the thymus. Stromal OP9 cells ectopically expressing the Notch ligand Delta-like1 mimic the thymic environment by inducing hemopoietic stem cells to undergo in vitro T cell development. Notch1 is also expressed on Pax5−/− pro-B cells, which are clonable lymphoid progenitors with a latent myeloid potential. In this study, we demonstrate that Pax5−/− progenitors efficiently differentiate in vitro into CD4+CD8+ αβ and γδ T cells upon coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
87
1
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 66 publications
5
87
1
2
Order By: Relevance
“…within hours of culture of Pax5 -/-pro-B cells on OP9-DL1 stroma. These findings imply a 'close link' between Notch signaling and upregulation of c-Kit in these progenitors, and this marked increase in cKit expression appears to be one of the earliest responses of T cell progenitors to Notch signaling [6,12].…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…within hours of culture of Pax5 -/-pro-B cells on OP9-DL1 stroma. These findings imply a 'close link' between Notch signaling and upregulation of c-Kit in these progenitors, and this marked increase in cKit expression appears to be one of the earliest responses of T cell progenitors to Notch signaling [6,12].…”
mentioning
confidence: 82%
“…First, Massa et al took advantage of a pro-B cell line that is blocked in its B cell potential by virtue of Pax5-deficiency (reviewed in [10]). This cell line retains multipotency in vivo and in vitro (reviewed in [11]) and was used here, and in a preceeding paper [12], to study the molecular requirements for Notch signaling for the generation of T or B cell lineages in vitro. Expression of c-Kit is low on Pax5 -/-pro-B cells, a property these cells share with 'normal' pro-B cells and various common lymphocyte progenitor phenotypes (see below).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Busslinger and colleagues [12] showed that Pax5 -/-pro-B cells also efficiently differentiated into the T cell lineage when cultured on OP9-DL1. In this study, these authors also demonstrated that as a consequence of Notch signaling, the Pax5 -/-pro-B cells rapidly upregulated the cell surface expression of c-kit.…”
Section: Introductionmentioning
confidence: 99%